(untitled) (International Journal of Technology and Management Research, 2021)
Delayed access to health care in terms of diagnosis and treatment has unforeseen health and cost implications on the patients and the public health system in general. Thus, the study examines patients’ waiting time in accessing health care services. The study employs a convenience sampling technique in collecting data from a sample of 350 Outpatients using a questionnaire. The main analytic tools used in the study are the paired sample t-test, binary logistic regression and SmartPLS structural equation modelling. Results from the study show that the actual waiting times of patients are generally higher than the expected times. Furthermore, the probability of a patient’s waiting time being rated as unacceptable is affected by the Day of attendance, Arrival time of patients, Large number of patients or long queue, Long registration time, Type of diagnosis, and Type of treatment sought. Finally, the study also establishes that there is no relationship between socio-demographic characteristics and unacceptable waiting time, as well as no relationship between hospital factors and unacceptable waiting time. Additionally, the study shows that unacceptable waiting time does not have any influence on overall patients’ satisfaction. However, a strong positive relationship between process factors and unacceptable waiting time was established. The study recommends that there is the need for health care policy formulators to adopt more efficient strategies, like use of computer modelling to help assign appointment time to patients, so as to significantly reduce the time patients spend waiting at the hospitals. Citation: Kunu, E. K. and Agbede, P. S. (2021). Statistical Analysis of Patients Waiting Time in Accessing Health Care Services in Ghana: A Case Study of University of Cape Coast Hospital. International Journal of Technology and Management Research. Vol. 6, Issue 1: 14－27. Received: October 23, 2020 Accepted: March 30, 2021